Distal Femoral Replacement for Periprosthetic Fractures around Total Knee Arthroplasty: When and How? - Khan, Saad; Schmidt, Andrew H. (The Journal of Knee Surgery, 2019)
Periprosthetic fractures around total knee arthroplasty have become more common with the increasing incidence of total knee arthroplasty. These fractures are challenging to treat, especially in older patients with poor bone stock. Although open reduction internal fixation remains the most common treatment, revision with distal femoral replacement has become popular in recent years. Careful evaluation and planning are required to have successful outcomes. We present a review of distal femoral replacement in periprosthetic fractures around the total knee arthroplasty, along with surgical technique, and pearls and pitfalls.
Keywords: distal femur periprosthetic fracture; revision total knee arthroplasty; distal femoral replacement